Analisis Metode Perancangan dan Evaluasi UI/UX: Sebuah Tinjauan Literatur Sistematis - Richi, Michael; Gunawan, Jenifer; Michael, Michael; Farisi, Ahmad (Universitas Multi Data Palembang, 2025)
The swift development of technology has positioned User Interface (UI) and User Experience (UX) design as essential components for the success of digital products. This research aims to investigate the methods and tools used in designing and evaluating UI and UX through a Systematic Literature Review (SLR) conducted over the 2022–2024 period. Data were gathered via Google Scholar searches using the keyword